2017
DOI: 10.1038/s41598-017-16445-8
|View full text |Cite
|
Sign up to set email alerts
|

Simple eco-friendly synthesis of the surfactant free SnS nanocrystal toward the photoelectrochemical cell application

Abstract: A simple, low cost, non-toxic and eco-friendly pathway for synthesizing efficient sunlight-driven tin sulfide photocatalyst was studied. SnS nanocrystals were prepared by using mechanical method. The bulk SnS was obtained by evaporation of SnS nanocrystal solution. The synthesized samples were characterized by using XRD, SEM, TEM, UV-vis, and Raman analyses. Well crystallized SnS nanocrystals were verified and the electrochemical characterization was also performed under visible light irradiation. The SnS nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Therefore, cheap and eco-friendly wide-bandgap metal oxides such as TiO 2 , BiVO 4 , or Fe 2 O 3 are considered inappropriate for the bottom electrode, requiring a narrow bandgap semiconductor. Over the last decades, different cost-effective metal chalcogenides such as Nanomaterials 2021, 11,52 2 of 14 tin sulfide (SnS, E g~1 .3 eV) [6,14] and copper-zinc-tin-sulfide (CZTS, E g~1 .5 eV) [10,15] or metal oxide materials, e.g., CuFeO 2 (E g~1 .5 eV) [16] have been tried with limited success. Although the optoelectronic properties of CZTS give the impression of being suitable for the bottom photoelectrode, the low photocorrosion stability restrains its applicability in commercial PEC water splitting devices [10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, cheap and eco-friendly wide-bandgap metal oxides such as TiO 2 , BiVO 4 , or Fe 2 O 3 are considered inappropriate for the bottom electrode, requiring a narrow bandgap semiconductor. Over the last decades, different cost-effective metal chalcogenides such as Nanomaterials 2021, 11,52 2 of 14 tin sulfide (SnS, E g~1 .3 eV) [6,14] and copper-zinc-tin-sulfide (CZTS, E g~1 .5 eV) [10,15] or metal oxide materials, e.g., CuFeO 2 (E g~1 .5 eV) [16] have been tried with limited success. Although the optoelectronic properties of CZTS give the impression of being suitable for the bottom photoelectrode, the low photocorrosion stability restrains its applicability in commercial PEC water splitting devices [10].…”
Section: Introductionmentioning
confidence: 99%
“…the formation of undesirable detrimental phases during processing, could pose a major obstacle to large-scale commercialisation. In recent years, various low-cost semiconductors have emerged, such as Cu 2 S (E g~1 .5 eV) 13 , CuFeO 2 (E g~1 .5 eV) 14 , CuBi 2 O 4 (E g~1 .7 eV) 15 , CuSbS 2 (E g~1 .5 eV) 16 , and SnS (E g~1 .3 eV) 17 . However, none of them have satisfied all the requirements for an ideal semiconductor for PEC water splitting.…”
mentioning
confidence: 99%
“…It has been reported that the large sheet-like morphology of layered 2D materials such as MoS 2 , SnS, SnSe, SnS 2 , etc. and their heterojunctions show high photocatalytic (PC) performance. The layered TiSe 2 has a higher work function (φ = 5.4 eV) than most of semiconductors, which can achieve better charge separation through constructing an electron bridge by making a supported layer coupled with another photoactive material. Once a photoelectron is generated in the photocatalyst, TiSe 2 could serve as an ideal electron sink and/or electron transport bridge to facilitate charge separation, leading to enhanced performance of the overall water-splitting reaction. , In a recent study, Kovalska et al reported the PEC/PC properties of tantalum disulfide (TaS 2 ) that belongs to the same family of TiSe 2 by using a three-electrode PEC setup in 0.5 M Na 2 SO 4 electrolyte under different laser light sources .…”
Section: Introductionmentioning
confidence: 99%